Influence of playing position and laterality in centripetal force and changes of direction in elite soccer players - Granero-Gil, P.; Gómez-Carmona, C. D.; Bastida-Castillo, A.; Rojas-Valverde, D.; de la Cruz, E.; Pino-Ortega, J. (PLOS ONE, 2020)
The purpose of the present study was to: (a) assess centripetal force (CentF) and changes of direction (COD) in elite soccer players according to playing position (central defender, CD; lateral defender, LD; central midfielder, CM; lateral midfielder, LM; forward, FW), laterality (right-footed vs. left-footed) and field zone (central vs. lateral), and (b) analyze the relationship between anthropometric characteristics (age, weight, height, body mass and fat mass) and non-linear locomotion workload. Thirty professional soccer players (age: 26.57±5.56 years) were tracked during the 2017-2018 season during friendly, national and international matches (38 total games) using inertial measurement devices. CentF and COD were the variables extracted for analysis. A one-way ANOVA was used for playing position comparison, a t-test for laterality and field zone, and Pearson`s correlation coefficient to analyze relationships between anthropometric characteristics and dependent variables. There were differences by playing position in COD (556.33-to-412.18), R20COD (484.36-to-354.81) and R60COD (48.38-to-38.61) (p < .01; Omegap2 = 0.03-to-0.05; CD>CM>LD>LM = FW); in CODHIA (49.75-to-37.11), R20CODHIA (16.04-to-9.11) and R60CODHIA (10.64-to-9.11) (p < .01; Omegap2 = 0.03-to-0.07; CM>FW>LM>CD = LD); in CODSPRINT (14.56-to-8.40) and R20CODSPRINT (3.29-to-1.40) (p < .01; Omegap2 = 0.03-to-0.04; FW = LM = CM>CD = LD); and in CentFMAX both in clockwise (992.04-to-902.09N) and counterclockwise (999.24-to-872.61N) directions (p < .02; Omegap2 = 0.02-to-0.07; FW = CD>CM = LM = LD). The highest values of counterclockwise CentF were performed by left-footed players in the central zone (p < .001; d = 0.71-to-1.44) and clockwise CentF by right-footed players (p < .001; d = 0.04-to-0.55) in the lateral field zone. Moderate correlations were found between age, body mass and high intensity/sprints COD and repeated COD ability (p < .05; r = 0.235-to-0.383). Therefore, team staff should consider anthropometric characteristics, playing position, laterality and field zone to individualize training workload related to non-linear locomotion in soccer.